DETEKSI DINI KELUHAN YANG LAZIM MUNCUL PADA LANSIA DI UPT PESANGGRAHAN PMKS MOJOPAHIT KABUPATEN MOJOKERTO - Mujiadi; Siti Rachmah; Nurul Mawaddah; Ika Suhartanti; Atikah Fatmawati; Fitria Wahyu Ariyanti; Anndy Prastya; Ike Prafita Sari; Yudha Laga Hadi Kusuma; Dwi Harini Puspitaningsih (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2024)
The decision to live at Pesanggrahan PMKS Mojopahit can come from the family or the wishes of the elderly themselves. Many elderly people experience physical and psychological complaints, some of which cannot be conveyed. Sometimes this complaint will cause depression. At this time, early detection of these complaints is needed. The method used for physical health examination is blood pressure measurement, a simple laboratory form random blood sugar levels and uric acid levels, mental health using a questionnairegeriatric depression scale. The target is all 48 elderly people at Pesanggrahan PMKS Mojopahit. The results show that the blood pressure of the elderly has a tendency to increase starting from grade 1 to grade 2 hypertension and isolated systolic hypertension as much as 29%. Uric acid levels show that the majority have uric acid levels within normal limits (56%), but 36% have uric acid levels that are high. high, blood glucose levels tend to lead to pre-diabetes mellitus as much as 21% and as many as 12% of elderly people have diabetes mellitus status. The results of mental health detection using GDS show that the majority of elderly people experience moderate depression. It is hoped that the management of the PMKS Mojopahit guesthouse will pay attention to these findings with the following steps; regular check-ups to maintain the health of the elderly, physical activity, leisurely walking and cardio exercise for the elderly, treatment of depression problems through group activity therapy and psychoreligious therapy.